Catalytic effect of MgFe2O4 on the hydrogen storage properties of Na3AlH6–LiBH4 composite system. (8th November 2018) - Halim Yap, F.A.; Ali, N.A.; Idris, N.H.; Ismail, M.
Abstract: The effect of MgFe2 O4 on the hydrogen storage properties of the composite Na3 AlH6 4LiBH4 was studied for the first time, where it was found that MgFe2 O4 addition decreased the onset desorption temperature of Na3 AlH6 4LiBH4 . Hydrogen (∼9.5 wt%) was released in three stages and the dehydrogenation temperatures were reduced to 80 °C, 350 °C, and 430 °C for the first, second, and third stage, respectively. The absorption kinetics of Na3 AlH6 4LiBH4 was also significantly improved due to the catalytic effect of MgFe2 O4 . Using Kissinger analysis, the apparent activation energies of decomposition of the Li3 AlH6 and NaBH4 stages in Na3 AlH6 4LiBH4 -10 wt% MgFe2 O4 were calculated to be 72 and 141 kJ/mol, respectively. These values were considerably lower than the corresponding values for the undoped composite. X-ray diffraction analysis revealed the formation of new products such as MgO and Fe during the heating process. Our results suggest that MgFe2 O4 enhanced the hydrogen storage properties of Na3 AlH6 4LiBH4 through the formation of active species, such as MgO and Fe. Highlights: The sorption properties of MgFe2 O4 -doped Na3 AlH6 –LiBH4 have been investigated. The dehydrogenation temperature of Na3 AlH6 –4LiBH4 was reduced to 100 °C. The Ea of MgFe2 O4 -doped Na3 AlH6 –4LiBH4 were found to be 72 kJ/mol and 141 kJ/mol. The formation of new products, MgO and Fe is considered play a synergetic catalytic role.